Tropylium-promoted Ritter reactions. Issue 71 (16th August 2021) - Doan, Son H.; Hussein, Mohanad A.; Nguyen, Thanh Vinh
Abstract : The tropylium ion serves as an excellent and environmentally-benign catalyst for the Ritter reaction. Abstract : The Ritter reaction used to be one of the most powerful synthetic tools to functionalize alcohols and nitriles, providing valuable N -alkyl amide products. However, this reaction has not been frequently used in modern organic synthesis due to its employment of strongly acidic and harsh reaction conditions, which often lead to complicated side reactions. Herein, we report the development of a new method using salts of the tropylium ion to promote the Ritter reaction. This method works well on a range of alcohol and nitrile substrates, giving the corresponding products in good to excellent yields. This reaction protocol is amenable to microwave and continuous flow reactors, offering an attractive opportunity for further applications in organic synthesis.